2017
DOI: 10.30699/ijp.2017.25037
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of Helicobacter pylori Infection in Neyshabur, Iran, During 2010-2015

Abstract: Backgrounds & Objective: The Helicobacter pylori prevalence has continuously decreased during recent years in Iran. The current study aimed at determining H . pylori prevalence in Neyshabur city, Northeast Iran, during 2010-2015. Methods: The current epidemiologic survey was conducted in Neyshabur from 2010 to 2015 to determine the prevalence of H. pylori infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…These findings are in agreement with several studies which found a significant effect of age increase on the levels of H. pylori seropositive cases (44,45), whilst others indicated contrasting results (38,46). In terms of gender, similar to an earlier study, no significant association was observed between IgG and IgA levels and sex, but positive cases of IgM were significantly higher in women compared to men (42). However, there is a conflict between our results and another study, which indicated higher IgG, IgM, and IgA seroprevalence cases in men compared with women (45).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings are in agreement with several studies which found a significant effect of age increase on the levels of H. pylori seropositive cases (44,45), whilst others indicated contrasting results (38,46). In terms of gender, similar to an earlier study, no significant association was observed between IgG and IgA levels and sex, but positive cases of IgM were significantly higher in women compared to men (42). However, there is a conflict between our results and another study, which indicated higher IgG, IgM, and IgA seroprevalence cases in men compared with women (45).…”
Section: Discussionsupporting
confidence: 75%
“…However, other studies found 18% and 67.4%, which are inconsistent with our results (40,41). The IgM results were in accordance with those studies, reporting that 2.4%, 5.2%, and 5.81% of the subjects were positive for H. pylori (37,42,43). On the other hand, IgM seropositivity was 16.1% and 34.9% in some studies (44,41) that are inconsistent with our findings.…”
Section: Discussioncontrasting
confidence: 73%
“…During the last decade, while several studies in Africa have described fluctuating trends in H. pylori seropositivity [16, 17], this has not been very much the same elsewhere, with a study in Iran reporting a constant trend from 2010 to 2015 [28].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a cross‐sectional study in Northeast Iran conducted from 2010 to 2015, and involving 11 596 participants were reported by Salehi et al . The H. pylori IgG antibody positivity was 72.8%; no change in the seroprevalence was observed during the study period.…”
Section: Global Prevalence Of Helicobacter Pylori Infectionmentioning
confidence: 99%